Immunological predictors of disease severity in patients with COVID-19. (September 2021) - Al Balushi, Asma; AlShekaili, Jalila; Al Kindi, Mahmood; Ansari, Zainab; Al-Khabori, Murtadha; Khamis, Faryal; Ambusaidi, Zaiyana; Al Balushi, Afra; Al Huraizi, Aisha; Al Sulaimi, Sumaiya; Al Fahdi, Fatma; Al Balushi, Iman; et al.
Highlights: Predictors of COVID-19 severity will help prioritize resources and minimize mortality. Immunological markers can be used as predictors of a poor prognosis. High IL-6 independently predicts poor outcomes in COVID-19 patients. A high percentage of large inflammatory monocytes predicts worse COVID-19 outcomes. Lower circulating naïve CD4+ T cells predicts a poor prognosis in COVID-19 patients. Abstract: Background: Identifying the immune cells involved in coronavirus disease 2019 (COVID-19) disease progression and the predictors of poor outcomes is important to manage patients adequately. Methods: This prospective observational cohort study enrolled 48 patients with COVID-19 hospitalized in a tertiary hospital in Oman and 53 non-hospitalized patients with confirmed mild COVID-19. Results: Hospitalized patients were older (58 years vs 36 years, P < 0.001) and had more comorbid conditions such as diabetes (65% vs 21% P < 0.001). Hospitalized patients had significantly higher inflammatory markers ( P < 0.001): C-reactive protein (114 vs 4 mg/l), interleukin 6 (IL-6) (33 vs 3.71 pg/ml), lactate dehydrogenase (417 vs 214 U/l), ferritin (760 vs 196 ng/ml), fibrinogen (6 vs 3 g/l), D-dimer (1.0 vs 0.3 μg/ml), disseminated intravascular coagulopathy score (2 vs 0), and neutrophil/lymphocyte ratio (4 vs 1.1) ( P < 0.001). On multivariate regression analysis, statistically significant independent early predictors of intensive care unit admission or death were higher levels of IL-6 (odds ratio 1.03, P  = 0.03), frequency of large inflammatory monocytes (CD14+CD16+) (odds ratio 1.117, P  = 0.010), and frequency of circulating naïve CD4+ T cells (CD27+CD28+CD45RA+CCR7+) (odds ratio 0.476, P  = 0.03). Conclusion: IL-6, the frequency of large inflammatory monocytes, and the frequency of circulating naïve CD4 T cells can be used as independent immunological predictors of poor outcomes in COVID-19 patients to prioritize critical care and resources.